Analysis Of Institutional Actors In Rice Policy Implementation In South Sulawesi Province, Indonesia - Tamba, La; ., Suratman; Azis, Alwi; Bailusy, Kausar (Advances in Social Sciences Research Journal, 2015)
The purpose of this study is to analyze the actor role and evaluation of its performance in the rice policy implementation in the South Sulawesi Province. This study uses institutional theory to explain the role of actors in the rice policy implementation. The study used qualitative research methods with the case study strategy. By pairing pattern analysis and making explanations techniques, the role of institutional actors in the rice policy implementation in two sample districts in South Sulawesi has not been effective. This can be shown by the farmers as a target group of this policy can only survive, yet gain a significant advantage in agricultural production. This is caused by the actors are in the bureaucratic system oriented rules.